Rol de los residuos sólidos municipales en el desarrollo de la pequeña industria y agricultura en el sector iquitos nauta-peru -2007-2008 - Guerra Sangama, Wilson (2008)
The management of solid waste located in the heart of wet tropical areas in the jungle is an important element as it is related with less pollution even with the availability of natural resources in order to improve work condition and people’s lifestyle. This thesis states that the conditions (composition waste) and results of the solid degrading waste in the landfills of Iquitos city is a potential source of stock of energetic resources in the wet tropical woods. A remarkable element was observed and shows that the ground of the landfills that has been provided with solid waste doesn’t contain enough nutritional elements that make up a great contribution in the improvement of the ground. However, there are ways of treatment of the solid waste and using them can contribute to the compost and the increasing stock of resources. The biogas that is generated through the solid degrading waste has as a main component the Methane (CH4) which has been estimated according to the Central America Model, the generated Methane gas increases the stock of energetic resources available in this area. The thesis concludes with a process proposal to elaborate compost from the solid waste, improving the nowadays situation in the treatment of this waste and also with the proposal to take actions in the use of Methane gas generated in the landfills.